A Systematic Review of Risk Management Tools and Techniques in Software Projects - Fadhli Luthfiansyah; Prasetyo, Aji; Raharjo, Teguh (The Indonesian Journal of Computer Science, 2024)
The crafting of software is a continual procedure, and the success of each step of that process is contingent on effective management. Despite this, numerous organizations need help developing e-service systems, frequently dealing with budget constraints and tight deadlines. The lack of focus on risk management in software projects is likely to blame for these failures. Management of risks is crucial to ensuring the success and efficacy of software development projects, as it assists in identifying areas of vulnerability and provides valuable insights into the project's most important aspects. This study identifies and analyzes tools and techniques to support software development projects’ risk management activity. A systematic literature review (SLR) methodology was employed to collect and evaluate relevant research articles. The findings highlight various risk management tools and techniques, including brainstorming, root cause analysis, risk probability assessment, artificial intelligence, and risk response planning. These tools and techniques contribute to identifying, analyzing, planning, and controlling risks in software projects. The research provides insights into the state of the art in risk management. It complements previous studies by offering practical guidance on software development project risk management tools and techniques.